2016
DOI: 10.1007/s00264-016-3357-2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive injection of peri-articular-multimodal drug for post-operative pain management in total knee arthroplasty: a double-blind randomized clinical trial

Abstract: Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…In fact, some researchers even suggest that using periarticular or intra‐articular infiltration analgesia without nerve block could provide good postoperative pain relief results . Recently, multiple studies have shown the pain relief efficacy of multimodal local injection of analgesics for TKA . Choosing an optimum drug composition for local injection, therefore, should be thoroughly considered as a meaningful procedure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, some researchers even suggest that using periarticular or intra‐articular infiltration analgesia without nerve block could provide good postoperative pain relief results . Recently, multiple studies have shown the pain relief efficacy of multimodal local injection of analgesics for TKA . Choosing an optimum drug composition for local injection, therefore, should be thoroughly considered as a meaningful procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetics such as ropivacaine and bupivacaine, along with epinephrine, are most commonly combined for use in local infiltration analgesia . Use of NSAIDs and morphine for the local injection has been reported to reduce postoperative pain . The use of corticosteroids has effects that cause concern in total joint surgery, such as a suppressive effect in prosthetic joint infection .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations